Modeling, Parameters Identification, and Control of High Pressure Fuel Cell Back-Pressure Valve. (16th November 2014) - Chen, Fengxiang; Liu, Ling; Liu, Shiguang; Zhang, Tong
Abstract : The reactant pressure is crucial to the efficiency and lifespan of a high pressure PEMFC engine. This paper analyses a regulated back-pressure valve (BPV) for the cathode outlet flow in a high pressure PEMFC engine, which can achieve precisely pressure control. The modeling, parameters identification, and nonlinear controller design of a BPV system are considered. The identified parameters are used in designing active disturbance rejection controller (ADRC). Simulations and extensive experiments are conducted with the xPC Target and show that the proposed controller can not only achieve good dynamic and static performance but also have strong robustness against parameters' disturbance and external disturbance.